A Novel Gold Calreticulin Nanocomposite Based on Chitosan for Wound Healing in a Diabetic Mice Model - Hernández Martínez, Sara Paola; Rivera González, Teodoro Iván; Franco Molina, Moisés Armides; Juan José Bollain y Goytia de la Rosa, Juan José; Martínez Sanmiguel, Juan José; Zárate Triviño, Diana Ginette; Rodríguez Padilla, Cristina (2019)
Thedevelopmentofnewnanomaterialstopromotewoundhealingisrising,becauseoftheirtopicaladministrationandeasyfunctionalizationwithmoleculesthatcanimproveandacceleratethe processofhealing.Ananocompositeofgoldnanoparticles(AuNPs)functionalizedwithcalreticulinwassynthetizedandevaluated.Theabilityofthenanocompositetopromoteproliferationandmigrationwasdeterminedinvitro,andinvivowoundhealingwasevaluatedusingamicemodelofdiabetesestablishedwithstreptozotocin(STZ).Invitro,thenanocompositenotaffectthecellviabilityandtheexpressionofproliferatingcellnuclearantigen(PCNA).Moreover,thenanocompositepromotestheclonogenicityof keratinocytes,endothelialcells,andfibroblasts,andacceleratesfibroblastmigration.Invivo,micetreatedwiththenanocompositepresentedsignificantlyfasterwoundhealing. Thehistologicalevaluationshowed re-epithelization and the formation of granular tissue, as well as an increase of collagen deposition. Therefore,theseresultsconfirmtheutilityofAuNPs–calreticulinnanocompositesaspotentialtreatment forwoundhealingofdiabeticulcers